Integrating Visualization Tools into the Requirements Engineering Process: An Empirical Study. Issue 3 (3rd July 2018) - Logan, Bradford; Dever, Jason; Stuban, Steven M.F.
Abstract: Engineers require new tools to meet the challenges of increasing system complexity, and visualization tools may present promising solutions to enhancing an individual's ability to analyze highly complex systems. Integrating visualization could provide managers with the opportunity to influence change early, minimizing cost and schedule impacts. This article provides an empirical evaluation of the potential impact that implementing requirements visualization tools can have on projects. The study, based on a sampling of 145 subjects, compares participants' ability to recognize relationships expressed in traditional requirements format versus integrating a visualization format. The study's results indicate significant improvement with graphical format employment.